The Problem of Comorbid Socially Significant Infections Under The Conditions of The COVID-19 Pandemic - V. M. KOLOMIETS; N. A. POLSHIKOVA; A. L. KOVALENKO; E. P. PAVLENKO (Антибиотики и Химиотерапия, 2022)
The aim of the study. To analyze formation features of the epidemic situation for tuberculosis (TB) in the context of the COVID-19 pandemic in order to predict the further actions of medical organizations.Materials and methods. The data for the region for the last 5 years (2017–2021) were analyzed, including 1,762 newly diagnosed cases of patients with TB and comorbidities (according to the data of the Regional Public Health Organization «Regional Clinical Anti-Tuberculosis Dispensary»). All cases were verified using standard diagnostic methods, including molecular genetic methods, to determine the resistance of pathogens to antibacterial drugs.Results. It was revealed that the epidemiological situation in the region was multidirectional: thus, during the COVID-19 epidemic, the most pronounced incidence decrease was observed among cases of chronic course hepatitis (by 16.4 times), while among patients with tuberculosis the incidence decreased by 2.75 times, and among patients with acute hepatitis — only by 1.5 times (P<0.05). Among the cases of comorbid infection, the most severe course was observed in patients with combined (TB + HIV) infection: there was both a more severe general condition, and the development of adverse (undesirable) reactions to anti-TB drugs, which required an extension of maintenance therapy.Conclusions. The results of the study showed that against the background of the COVID-19 pandemic in the region, there was no tendency towards a worsening of the epidemic situation, primarily for the more socially significant infection — tuberculosis. At the same time, there was an increase in the number of cases of comorbid pathology, including HIV + TB. In the treatment of patients with comorbid forms of infection, it is necessary to take into account the possibility of developing hepatotoxic reactions and, as a result, the appointment of accompanying drugs with hepatoprotective and detoxification effects in therapy.